Development of UV/HPLC methods for quantitative analysis of benznidazole in human plasma and urine for application in pediatric clinical studies - Marson, María Elena (2013)
Objective: Chagas disease constitutes a major public health problem in Latin America. Correctly designed pharmacokinetic, safety, and bioequivalence studies are desirable in order to fill the knowledge gaps that presently exist on available drugs. It is necessary to develop accurate, simple, reproducible, and sensitive high-performance liquid chromatography (HPLC)/UV methods for the quantization of benznidazole (BNZ) in human plasma and urine for clinical applications, specially in pediatric patients. Methods: Quantization of BNZ in human plasma involved freeze-drying and re-suspension in organic solvent followed by reverse phase HPLC with UV detection. Analysis of BNZ in urine involved liquid/liquid extraction followed by reverse phase HPLC with UV detection. RESULTS: Limits of quantization (LOQ) were 0.32 μg/ml for plasma and 5.2 μg/ml for urine. No metabolite interferences were showed in both methods. Conclusion: The LOQ of methods seems appropriate in pediatric clinical contexts. Both procedures were applied with good results, to the quantization of BNZ in plasma and urine of patients treated for Chagas disease.